Pelatihan Pemanfaatan Ekstrak dari Limbah Eceng Gondok pada Pembuatan Hand Sanitizer sebagai Antiseptik Alami - Haniif Prasetiawan; Bayu Triwibowo; Maharani Kusumaningrum; Zuhriyan Ash Siddieqy Bahlawa; Dewi Selvia Fardhyanti; Dewi Artanti Putri (Unika Santu Paulus Ruteng, 2022)
This article aims to describe the use of water hyacinth leaves as an ingredient for making hand sanitizers or natural antiseptic gels. Water hyacinth leaves will not cause microbial resistance due to the complexity of water hyacinth leaves containing flavonoids (luteolin, apigenin, tricin, chrysoeriol, kaempferol, azaeleatin, gossypetin, and orientin) and tannins contained in water hyacinth leaves are proven to be effective as antibacterial and antimicrobial agents. Based on this potential, water hyacinth leaves are very likely to be used as a natural antiseptic. The hand sanitizer produced in this activity has gone through a preference test on the community by looking at the preferences for color, thickness, moist impression, aroma (fragrance), and packaging. The teenager community in the RW 027, Batursari, Mranggen District, Demak Regency. With this activity, the teenager community can gain knowledge about the use of water hyacinth leaf extract as a natural hand sanitizer that is environmentally friendly and can make hand sanitizer products independently. Thus, the application of making water hyacinth leaf extract hand sanitizer can be applied in the area.